Recent developments in the therapeutics of SARS-CoV-2 infection - Priyanka Nagu; Arun Parashar; Pankaj Sharma; Vineet Mehta (​​​One Health Bulletin)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly transmittable respiratory virus that causes COVID-19 disease. Since its emergence in the early 2000s, SARS has posed significant public health challenges and continues to be a concern. This review provides an overview of current treatment strategies for SARS-CoV and explores the potential utility of herbal molecules in combating this viral infection. The primary treatment approach for SARS-CoV has historically centered on supportive care, which includes oxygen therapy, mechanical ventilation, and antipyretic medications to manage symptoms. However, with the ongoing advancement of medical research and our evolving understanding of the virus, several antiviral drugs have been developed and repurposed to target SARS-CoV. Recent developments in the field of herbal medicine have drawn attention to the potential efficacy of natural compounds in the management of viral infections, including SARS. Herbal molecules, characterized by their diverse bioactive constituents, exhibit antiviral properties that could be harnessed to mitigate SARS symptoms and inhibit viral replication. Ocimum sanctum, Tinospora cordifolia, Zingiber officinale, Curcuma longa, Panax ginseng, and Aloe vera have been identified for their immunomodulatory effects. This review highlights promising herbal molecules such as quercetin, and curcumin, which have demonstrated antiviral effects in-vitro and in some preclinical studies. While current treatment strategies for SARS primarily rely on supportive care and antiviral medications, the exploration of herbal molecules presents an exciting avenue for potential adjunctive therapies. Further research is required to validate their efficacy, safety profiles, and mechanisms of action. A holistic approach that combines conventional medicine with herbal remedies may offer new insights into the treatment of SARS and other viral respiratory illnesses.